Model Pembiayaan Syariah Dalam Mengatasi Praktik Sistem Tebasan Di Sentra Padi Nasional - Nono Hartono (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The objectives of this study to identify the implementation of tebasan practices, analyze the contribution of the role of Islamic financial institutions and develop a sharia financing model to solve the practice of tebasan. The research method used with a qualitative approach, through interviews with farmers and Islamic financial institutions. The results showed that the practice of the tebasan in Indramayu had been carried out for a long time by the community, this was due to the lack of understanding of Islamic law which made the farmers continue to carry out the practice. In addition, the contribution of Islamic financial institutions to solved the practice has not yet existed. The absence of limited capital human resources and businesses that have large risks are the main factors of Islamic financial institutions have not contributed. Islamic finance which can be a solution to solve the practice of tebasan source non-commercial financing (Al-Qardhul Hasan) and commercial financing (Salam, Musyarakah or Mudharabah).